2009
DOI: 10.1111/j.1476-5381.2009.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts play key roles in the mechanisms of action of strontium ranelate

Abstract: Background and purpose: Strontium ranelate reduces fracture risk in postmenopausal women with osteoporosis. Evidence from non-clinical studies and analyses of bone markers in phase III trials indicate that this is due to an increase in osteoblast formation and a decrease of osteoclastic resorption. The aim of this work was to investigate, in human cells, the mechanisms by which strontium ranelate is able to influence the activities of osteoblasts and osteoclasts. Experimental approach: Human primary osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 58 publications
10
160
0
7
Order By: Relevance
“…Akt phosphorylation was measured in HOBs that were pre-treated with 500 nM (10 ϫ IC 50 ) NPS2143 for 5 min followed by the addition of 2 mM strontium for 10 min. (21). In the current study pre-treatment of HOBs with 50 nM wortmannin abolished strontium-induced Akt-Thr 308 phosphorylation but had little effect on strontium-induced Akt-Ser 473 phosphorylation (Fig.…”
Section: Strontium-induced Akt-thrsupporting
confidence: 50%
See 3 more Smart Citations
“…Akt phosphorylation was measured in HOBs that were pre-treated with 500 nM (10 ϫ IC 50 ) NPS2143 for 5 min followed by the addition of 2 mM strontium for 10 min. (21). In the current study pre-treatment of HOBs with 50 nM wortmannin abolished strontium-induced Akt-Thr 308 phosphorylation but had little effect on strontium-induced Akt-Ser 473 phosphorylation (Fig.…”
Section: Strontium-induced Akt-thrsupporting
confidence: 50%
“…4A). Dual-phosphorylation of Akt may explain the prosurvival effect of strontium that was previously reported (21). Knock-out mouse studies have shown that of the three isoforms of Akt, Akt1 regulates the control of osteoblast survival (45), whereas Akt2 promotes induction of differentiation prior to Runx2 expression (46).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, strontium ranelate, an approved antiosteoporotic drug, (27)(28)(29) was found to activate the CaSR in osteoblasts (30), resulting in activation of osteoblastic cell replication, differentiation, and survival (31,32). In OVX rats, strontium ranelate-treated animals exhibited increased bone formation and decreased bone resorption, resulting in prevention of trabecular bone loss, improved bone microarchitecture, and strength (33,34).…”
Section: Present Anabolic Therapiesmentioning
confidence: 99%